2011
DOI: 10.4238/2011.october.25.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissimilarity of putative gamma-ray-induced ‘Preciosa - AAAB-Pome type’ banana (Musa sp) mutants based on multivariate statistical analysis

Abstract: ABSTRACT. Bananas are among the most important fruit crops worldwide, being cultivated in more than 120 countries, mainly by small-scale producers. However, short-stature high-yielding bananas presenting good agronomic characteristics are hard to find. Consequently, wind continues to damage a great number of plantations each year, leading to lodging of plants and bunch loss. Development of new cultivars through conventional genetic breeding methods is hindered by female sterility and the low number of seeds. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
3
0
3
Order By: Relevance
“…Sudré et al (2010) UENF and set five as the optimal number of groups because the maximum value was reached at this point. Pestana et al (2011) analyzed 74 banana mutants and observed greater increases in the probability function in group III, which agrees with the findings of this study. In turn, Campos et al (2013) evaluated a population of 138 Psidium guajava individuals from the UENF breeding program and found that the greatest increase in the probability function was achieved when five groups were considered.…”
Section: Ward-mlm Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Sudré et al (2010) UENF and set five as the optimal number of groups because the maximum value was reached at this point. Pestana et al (2011) analyzed 74 banana mutants and observed greater increases in the probability function in group III, which agrees with the findings of this study. In turn, Campos et al (2013) evaluated a population of 138 Psidium guajava individuals from the UENF breeding program and found that the greatest increase in the probability function was achieved when five groups were considered.…”
Section: Ward-mlm Methodssupporting
confidence: 92%
“…These procedures have been used by Gonçalves et al (2009) in Solanum lycopersicum; Barbé et al (2010) in Phaseolus vulgaris;and Sudré et al (2010) in Capsicum spp. There are also reports of using this procedure to study banana (Pestana et al, 2011;Pereira et al, 2012) and guava (Campos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, trabalhos envolvendo aspectos socioeconômicos ligados aos sistemas de produção e à suscetibilidade natural das cultivares atualmente em uso pelos agricultores vêm sendo realizados. De maneira geral, buscam-se genótipos com resistência a doença, precocidade de produção, elevada produtividade, porte baixo, bom sistema radicular, eficiência no uso de água e nutrientes, e qualidade dos frutos (tamanho, forma, sabor e aroma) (PUA et al,2003;Silva et al, 2011a).…”
Section: Estratégias Para O Desenvolvimento De Novas Cultivaresunclassified
“…O PMGB da Embrapa desenvolveu as seguintes cultivares por meio de hibridação: BRS Caprichosa, BRS Garantida, BRS Japira, BRS Pacovan Ken, BRS Preciosa, BRS Princesa, BRS Tropical, BRS Vitória, BRS Pioneira e BRS Platina. Além dessas cultivares, foram recomendadas a FHIA 01 (BRS Maravilha), BRS Pelipita e BRS Thap Maeo (Mysore) (SILVA et al, 2011a). As cultivares mais utilizadas pelos agricultores brasileiros, Prata-Anã e Pacovan, também foram recomendadas pela Embrapa a partir da seleção de genótipos em sua coleção de germoplasma (ALVES et al, 1985).…”
Section: Introductionunclassified
See 1 more Smart Citation